Studi Eksperimental Pengaruh Panjang Lengan Massa Pemberat Dan Panjang Lengan Magnet Terhadap Respon Pendulum Lengan Ganda Dengan Peredam Arus Eddy - Mohammad Farid; Ardi Noerpamoengkas (Institut Teknologi Adhi Tama Surabaya, 2022)
Eddy current damping mechanism can be used in pendulum vibration systems by placing a magnet on the pendulum arm and bringing it close to a metal plate. This study uses a new pendulum model by separating the load mass and the magnet on two separate pendulum arms. The length of the load mass arm and the length of the magnet arm are varied. The magnet is brought close to the copper plate to get the Eddy current. The pendulum response was recorded with a video camera and processed using Tracker software. The results of data processing are the first response amplitude and the settling time. The shorter the arm of the load mass and the longer the magnetic arm, the smaller the first response amplitude and the faster the settling time.Kata kunci: Damper, Eddy current, pendulum, vibration.